Implementasi Audio Steganografi menggunakan 4th LSB dan Advanced Encryption Standard pada Windows Phone - M. Chaeril Maricar; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Securing data during transmission become one of the problem in technology, those data can be intercepted and read by others. One preventive action to overcome this is by using steganography. This thesis implements an audio steganography using Windows Phone. Combination of Advanced Encryption Standard to secure data and Audio Wave Steganography which embedded data inside 4th LSB layer, resulting in increased safety and robustness against noise addition compared to 1st LSB. Index Terms—Advanced Encryption Standard, Audio Steganography, Audio Wave Steganography, Least Significant Bit, Windows Phone.